Numerical investigation on turbulent flow and heat transfer characteristics of ferro-nanofluid flowing in dimpled tube under magnetic field effect - Tekir, Mutlu; Arslan, Kami̇l; Gedik, Engin; Pazarlıoğlu, Hayati Kadir; Gürdal, Mehmet (Elsevier BV, 2022)
Abstract For the aim of increasing the heat transfer enhancement, a hybrid method in which active and passive heat recovery techniques have been used together. The usage of nanofluid, MHD and dimpled fins tube have not been utilized together so far. Regarding this issue, this study is the first numerical study to determine effect of usage of three effects together comprehensively. In this study, thermo-hydraulic performance of Fe3O4/H2O nanofluid (ferro-nanofluid) flow inside dimpled tube under magnetic field effect has been examined numerically. The main purpose of the study is to obtain numerical data for turbulent flow in the spherical dimpled tubes providing some aid to design a highly efficient thermal energy storage devices. Dimple geometry with nondimensional pitch ratio (P/d = 3.75, 7.50 and 11.25), Hartmann number (Ha = 75, 150, 225) and nanoparticle volume fraction ( φ = 0.5, 1.0 and 2.5 vol%) are the parameters investigated in this study. The numerical analyses have been carried out Reynolds number ranging from 10,000 to 50,000 at a constant heat flux at 20 kW/m2. The simulations have been built up by Realizable k- e turbulence model and single-phase approach. Also, “MagnetoHydroDynamic” (MHD) module has also been activated for defining magnetic field effect. The results showed that Nusselt number increases with increasing Reynolds number and decreasing pitch ratio. The dimple geometry type of P/d = 7.50 has been determined as the most efficient dimple geometry type. In the case of highest magnetic field intensity, the highest Nusselt number increment (72.48%) has been obtained for φ = 2.5 vol% compared to the base fluid of distilled water using as the working fluid for smooth tube. The highest PEC value was also obtained as 1.126 for the case of P/d = 7.5, φ = 2.5 vol% and Ha = 75. In addition, the effect of magnetic field intensity on velocity and temperature distributions has been presented with contour graphs.
Keywords: 7. Clean energy